The Problem of the Classification of Temporal Adverbs in Modern English - Василенко, Ольга Вікторівна; Vasylenko, Olha V.; Кухарук, Тетяна Михайлівна; Kukharuk, T. M. (Vinnytsia Pedagogical Institute, 1998)
Посеред великої кількості часових значень слово "час" є найбільш містким, оскільки предмет цього знака і поняття співпадають. Отже,"час" - це категоріальне слово. Прислівники часу мають слово "час" в одному із своїх лексико-семантичних варіантів. Among a great number of temporal meanings the word “time” is the most capacious as the subject of this sign and its notion coincide. So “time” is a categorical word. The temporal adverbs have the word “time” in one of their lexico-semantic variants. Classifying the adverbs of time into lexico-semantic groups linguists have different points of view.
Keywords: семантична классифікація; semantic classification; прислівники часу; temporal adverbs